Detection of human serum albumin by room temperature nematic liquid crystals based on polarising microscopy, molecular docking and Raman spectroscopy. Issue 6 (3rd May 2022) - Kalita, Priyanki; Bhattacharjee, Ayon
ABSTRACT: Liquid crystal-based biosensors serve an essential role to detect biomolecules and chemical events as an effective, and simple detection tool. A biosensor that works on the principle of orientational reordering of liquid crystal molecules in presence of protein is reported. We employ a liquid crystal 4´-pentyl-4-biphenylcarbonitrile to detect the protein human serum albumin using multiple techniques. The composite of liquid crystal and protein forms nematic droplets. The transitions in the radial to bipolar configuration of the droplets are investigated via polarising optical microscopy. The detection limit is determined to be 100 µM. The interaction between protein and liquid crystal is performed through molecular docking . The binding sites, active residues, and binding energies are also calculated from the analysis. The binding energy required to bind 5CB with HSA at this site is −8.10 Kcal/mol. Raman spectroscopy is performed to determine the vibrational changes in the active residues, conformations of the disulphide bonds of the protein, which developed during the interaction with the liquid crystal. Raman spectroscopic studies confirm the interactions between the active residues of HSA and 5CB. The Raman parameters are studied at different HSA concentrations. This report demonstrates the applications of liquid crystals as transducing element in biosensing field. Graphical abstract: uf0001